‘No to Khudoni Hydropower Plant!’ – Social Movement in Georgia - Dundua, Salome; Karaia, Tamar (Politics / პოლიტიკა; 2019: მეოთხე ნომერი, 2020)
Social movement and social changes study is relatively new academic field in post Soviet Georgia. We chose “No to Khudoni Hydropower Plant!” – Social Movement case study for several reasons. On one hand, Khudoni PHH falls under the category of gigantic hydropower plants in Georgia and planned to be built in Svaneti, the region with special local natural and climate conditions; On another hand Khudoni HPP is one of the fewest continuous active and inclusive movements in Georgia that has been progressing throughout years (from 1979) with participation of various actors from public and political communities.   Within the research we rely on the theory of structural functionalism that attempts to explain that movements are formed not by actors, but are conditioned by social and political situation. As the result of the process of “Perestroika” and “Glasnost”, political, cultural, economic and social changes were underlaid to civic activism.    The research aims to determine: Why  the issue of Khudoni  grew into a social movement; What is the degree of participation of different actors; who determines directionality of the process and how these actors communicate? Analyzing the issue it became evident that the arguments of the proponents of Khudoni HPP are about the prospective economic benefits of the project, while the arguments of the opponents of Khudoni construction is rather broad and entail not just environmental but social, cultural and ethno-linguistic arguments as well.